Challenges Facing Groundwater Management in Sudan - Abdo, Gamal; Salih, Abdin (University of Khartoum Engineering Journal, 2022)
Sudan has great potential of renewable and non-renewable groundwater resources which are important sources of water supply for domestic, industrial and agricultural uses. It is a key element for human settlement and sustained socioeconomic activities. Demand for groundwater in many areas of the Sudan has recently increased considerably in order to meet the needs for the implementation of agricultural and economic development plans but regrettably, these development are taking place in a rather unplanned manner leading to many problems such as overexploitation, reduction of reliable yield, and deterioration of quality .This emphasizes the need for sound polices and optimum plans for groundwater resources management in order to ensure its long term sustainability. However, Groundwater management in Sudan is faced with many challenges. The most obvious of these challenges is the absence of quantitative and qualitative monitoring and scarcity of information on aquifers geometry and their hydro geological characteristics. Another major difficulty is related to the understanding of flow dynamics and recharge sources and mechanisms for the different aquifers. This makes the estimation of recharge volumes an extremely difficult task. Correct estimation of groundwater recharge and aquifer storage are two of the most important requirements for long term management of any groundwater system. Fractured aquifers in Sudan cover very large areas and provide an important source of water particularly in rural areas. A major problem encountered in the management of fractured aquifers is the limited understanding of their hydrogeology and flow dynamics. The fractures characteristics could be extremely complex making it very difficult to locate areas of productive boreholes with sustainable groundwater yield. Vulnerability and risk of contamination of these aquifers are also very high. Other key challenges facing groundwater management in Sudan are the management of shared non-renewable aquifer resources, lack of comprehensive guiding plans and policies, poor governance and legislative framework, inadequate capacity, and lack of coordination among groundwater sub sectors.The purpose of this paper is to discuss these challenges in some details and suggest directions for overcoming them. The paper also includes a case study on the use of advanced methodologies for groundwater management and protection in Sudan.